Processing and Preservation of Okra Pickle (Progressive Agriculture, 2013)
The fresh okras were analyzed for proximate composition whereas the developed pickles were analyzed for proximate composition, microbiological status, sensory attributes and overall storage stability of the pickles. The proximate composition fresh okra was moisture 87.5%, ash 0.89%, total solid 18%, vitamin-C 11.1 mg/100g. According to the processing method, the compositions of developed pickles were different. The range of moisture content varied from 59.28% to 69.20% for pickle in sugar, oil and combination of both. Since sugar and salt were used, resulting losses in moisture content were observed in all the samples. Vitamin-C content was decreased or lost by oxidation and heat following first-order kinetics which states that concentration has exponential relationship with time. The microbiological studies revealed that total viable counts (bacteria) were high in pickles which was processed in sugar and low which was processed in oil and oil-sugar mixed, respectively. The acceptability of processed pickles was organoleptically evaluated by the panelists using 1-9 hedonic scale assigned marks for colour, flavour, texture and overall acceptability. The test score indicated that among three samples, the pickle which was processed in sugar and oil mixed (sample-3) was the most acceptable. Storage studies were carried out for up to six months at room temperature (27ºC-33ºC) at an interval of 1 month up to first 2 months and at an interval of 2 months for the consecutive 4 months. The result showed that moisture content decreased slightly with time. All the pickles became softer with the passing of time.DOI: http://dx.doi.org/10.3329/pa.v21i1-2.16777 Progress. Agric. 21(1 & 2): 215 - 222, 2010